Global studies of cadmium in relation to Theobroma cacao: A bibliometric analysis from Scopus (1996 -2020) - García, Ligia (2021)
The maximum cadmium tolerance standards were established by the European Union in 2014, for the importation of cocoa-based products, causing concern in the countries. Global studies on Theobroma cacao research related to cadmium activity in the atmosphere were analyzed. Bibliometric analyses in R and VOSviewer programs were used to examine 64 documents published in the Scopus database according to keywords. We identified 811 keywords in the co-occurrence of terms, 5 thematic groups in the bibliographic coupling, 20 institutions as most important affiliations, 20 countries of origin of corresponding authors, 112 institutions in co-authorship network of which 5 are in primary documents, and two groups in thematic similarity in co-citation of documents. The United States leads the scientific production with 11 papers, followed by Colombia (8) and Ecuador (7). In 1996, the first scientific article was registered for the network, with increases of up to 11 publications by 2020. In conclusion, the need to strengthen and create more research networks between countries, institutions, authors, and co-authors is evident. It is hoped that the results will allow a comprehensive unraveling of the cadmium-cocoa research trajectory, while at the same time yielding new prospective research.